Ответы и объяснения

2013-05-07T18:45:22+04:00

3) 4x-1,5x+7+1\frac{1}{7}x=2,5x+\frac{8}{7}x+7=2\frac{1}{2}x+\frac{8}{7}x+7=\\\\\=\frac{5}{2}x+\frac{8}{7}x+7=\frac{35}{14}x+\frac{16}{14}x+7=\frac{51}{14}x+7=3\frac{9}{14}x+7

Значит нужно подставить вместо * -3\frac{9}{14}x

3\frac{9}{14}x+7-3\frac{9}{14}x=7 - выражение не содержит переменной.

 

 

4) p(b)=2p_1(b)+p_2(b)=\\\\=2(12b^4-10b^2+7)+(1,4b^3-5b^4+b+1,2)=\\\\=24b^4-20b^2+14+1,4b^3-5b^4+b+1,2=\\\\=19b^4+1,4b^3-20b^2+b+15,2

 

 

p(b)=p_1(b)-3p_2(b)=\\\\=12b^4-10b^2+7-3(1,4b^3-5b^4+b+1,2)=\\\\=12b^4-10b^2+7-4,2b^3+15b^4-3b-3,6=\\\\=27b^4-4,2b^3-10b^2-3b+3,4